Intravital multiphoton imaging of mouse tibialis anterior muscle. Issue 2 (3rd May 2016) - Lau, Jasmine; Goh, Chi Ching; Devi, Sapna; Keeble, Jo; See, Peter; Ginhoux, Florent; Ng, Lai Guan
ABSTRACT: Intravital imaging by multiphoton microscopy is a powerful tool to gain invaluable insight into tissue biology and function. Here, we provide a step-by-step tissue preparation protocol for imaging the mouse tibialis anterior skeletal muscle. Additionally, we include steps for jugular vein catheterization that allow for well-controlled intravenous reagent delivery. Preparation of the tibialis anterior muscle is minimally invasive, reducing the chances of inducing damage and inflammation prior to imaging. The tibialis anterior muscle is useful for imaging leukocyte interaction with vascular endothelium, and to understand muscle contraction biology. Importantly, this model can be easily adapted to study neuromuscular diseases and myopathies.